Some Results in Stability Analysis of Hybrid Dynamical Systems - Santos, I.l.d.; Silva, G.n.; Silva, Geraldo Nunes [UNESP] (Brazilian Society for Computational and Applied Mathematics (SBMAC), 2011)
In this paper we introduced a general model for the Hybrid Dynamical Systems and for such systems we introduced the usual concept of Lyapunov stability. Furthermore, we established two Principal Lyapunov Theorems and a converse theorem.

Neste trabalho introduzimos um modelo geral para os Sistemas Dinâmicos Híbridos e para tais sistemas introduzimos o conceito usual de estabilidade de Lyapunov. Além disso, estabelecemos dois Teoremas Principais de Lyapunov e um teorema de convers˜ao.
Keywords: hydrid dynamical systems; Lyapounov stability; dIscontinuous dynamical systems